Q-Switched Ytterbium-Doped Fiber Laser Using Black Phosphorus as Saturable Absorber. (May 2016) - Al-Masoodi, A. H. H.; Ahmed, M. H. M.; Latiff, A. A.; Arof, H.; Harun, S. W.
Abstract : We demonstrate a Q-switched ytterbium-doped fiber laser (YDFL) using a newly developed multi-layer black phosphorous (BP) saturable absorber (SA). The BP SA is prepared by mechanically exfoliating a BP crystal and sticking the acquired BP flakes onto a scotch tape. A small piece of the tape is then placed between two ferrules and incorporated in a YDFL cavity to achieve a stable Q-switched operation in a 1.0μm region. The laser has a pump threshold of 55.1 mW, a pulse repetition rate that is tunable from 8.2 to 32.9 kHz, and the narrowest pulse width of 10.8 μs. The highest pulse energy of 328 nJ is achieved at the pump power of 97.6mW. Our results show that multi-layer BP is a promising SA for Q-switching laser operation.